Salbutamol in paediatrics: pharmacology, prescribing and controversies. Issue 4 (8th April 2016) - Andrzejowski, Paul; Carroll, Will
Abstract : Salbutamol has become a key drug in respiratory medicine since it was first developed by Sir David Jack et al in 1968, 5000 years after the β agonist ephedrine was first used in its raw form, as the Ma Huang herb in Chinese medicine to treat asthma. It is one of the most commonly encountered medicines in paediatric practice and the authors have found that an understanding of its pharmacology in clinical practice is incredibly helpful. In this article, we discuss its pharmacology and pharmacodynamics, practical prescribing points and some unresolved issues surrounding its use, which should serve to provide an essential working knowledge for the busy paediatrician.